Quantum plasmonic effects of double raman systems / Loh Wai Ming - Loh, Wai Ming (2017)
An analytical theory to study the optical properties of a hybrid nanostructure comprising of a metallic nanoparticle (MP) in close proximity with a quantum system (QS) in double Raman configuration is presented. In particular, the spectra of the quantum fields emitted by the system is computed to gain insights into the plasmonic effects caused by the nearby MP. Using Heisenberg-Langevin formalism, the quantum spectra of the Stokes and anti-Stokes fields emitted by a mesoscopic spherical particle (which consists of quantum particles in double Raman scheme) without the presence of a nearby MP is first computed. The dependence of the spectra on the particle size, laser configuration and angle of observation is then analyzed and studied. It is found that the mesoscopic nature of the microparticle hides or modifies the spectral peaks originally formed due to quantum coherence and laser interaction effects. The analytical calculation is then extended to include the plasmonic effects from a nearby MP, where the MP-QS interaction is modelled using a semiclassical approach in which the MP is treated as a classical spherical dielectric particle while the QS is treated quantum-mechanically using Heisenberg-Langevin formalism. Spectra of the quantum fields emitted by the hybrid nanostructure exhibit cavity interference effect which manifests itself as oscillations across interparticle distances. Besides, Fano dip in the central peak of the spectra is observed at sufficiently weak laser fields strengths, indicating enhancement of the local Stokes and anti-Stokes fields to the extent that the quantum fields become comparable to or greater than the incident laser fields strengths. Also, the MP-QS coupling, which is affected by the size of the MP and the number density of the QS, changes the angular dependence of the spectra by breaking the angular rotational symmetry. In the presence of Surface Plasmon Resonance (SPR) the oscillatory dependence of the spectra on the interparticle distance and angles of observation becomes even stronger due to the plasmonic enhancement effect. The study also includes the derivation of a general expression for the scattered electric field formula which takes into account the multipole effects and is valid for arbitrary size of the component particles as well as arbitrary observation distance. This expression is then applied to the study of MP-QS interaction with the aim of deriving a scattered field formula that is valid for any energy level configuration of the QS.